Arsenik: Online Monitoring System to Improve Efficiency and Effectivity for Hydroponic Farming Community in Gempol, Pasuruan - Prisma Megantoro; Muhammad Akbar Syahbani; Hafidz Faqih Aldi Kusuma; Sigit Dani Perkasa; Diaz Samsun Alif; Abdul Abror (Peneliti Teknologi Teknik Indonesia, 2022)
Hydroponics is one of the agricultural techniques with great potential for producing herbal products. Hydroponics is a kind of plant cultivation that is environmentally friendly and does not require a large amount of land. Hydroponics was developed a long time ago, but there are not many notable results in terms of quality and quantity. Improving the quality of agricultural products requires a step of modernization by implementing automation systems based on the Internet of Things. Therefore, the solution offered to overcome the problems of current hydroponics systems is green hardware namely Airlangga sahabat Petani Hidroponik (Arsenik). This firstly prototype hardware is real-time monitors the system, measuring various aspects such as the environment, ie; acidity level, total dissolve solids, water temperature, dissolve oxygen then translates them into visualization that can be read directly by the user. The expected result of this hardware is to enable communities to develop hydroponic systems and improve hydroponic crop yields by internet of things.